Nationalism and the international labor movement : the idea of the nation in socialist and anarchist theory - Forman, Michael, 1956- (Pennsylvania State University Press, 1998)
The resurgence of nationalism accompanying the decline of communism has been taken to indicate the failure of socialist theory to grasp the nature of this phenomenon. Against both those who argue that the radical tradition has ignored and underestimated nationalism and those who accuse it of economic reductionism, this careful analysis of the idea of the nation as it was developed in the work of the major thinkers of the international labor movement reveals evidence of how seriously they grappled with nationalism. Forman examines the relationships among ethnic and civic nationality, national self-determination, republican institutions, and the process of globalization from the perspective of the post-Soviet era and in the light of social theory and Kant's ideas about cosmopolitan right.